PERAN STRATEGIS KETUA YAYASAN DALAM PENGEMBANGAN UNIT USAHA PONDOK PESANTREN: STUDI KASUS DI PERGURUAN ISLAM GANRA - Rizki, Ahmad Abu; Firman, Firman; Wahidmurni, Wahidmurni (STKIP Pesisir Selatan, 2025)
This study aims to analyze the strategic role of the Foundation Chairman in developing business units at the Islamic Boarding School of Perguruan Islam Ganra. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the Foundation Chairman and business unit managers, direct observations of entrepreneurial activities, and document analysis of business reports and institutional archives. Data analysis consisting of data condensation, data display, and conclusion drawing/verification. Data validity was ensured through source and method triangulation, as well as peer debriefing. The findings reveal that the Foundation Chairman plays a central role in developing pesantren business units through three dimensions. First, as a policymaker, the chairman issues decrees that regulate organizational structure and unit responsibilities. Second, as a coordinator, the chairman provides guidance and delegates authority, thereby increasing managerial effectiveness and accountability. Third, as an external liaison, the chairman establishes strategic partnerships with government and stakeholders to secure funding, facilities, and entrepreneurial training. This study demonstrates that a participative-strategic leadership style of the foundation chairman is a critical factor in achieving pesantren’s economic independence.